Cyber Counseling Using the Riliv Platform as a Method to Improve Guidance and Counseling Services After the Covid-19 Pandemic - Mayfani, Silviedriya; Budiman, Nandang; Nadia Aulia Nadhirah (Student Scientific Creativity Journal, 2023)
This study aims to analyze the in-depth relationship with cyber counseling services using the Riliv platform and explain the code of ethics for online counseling. This research uses the method of literature review or literature study in the form of journal articles. The results of the study are known to make cyber counseling services considered effective because they can make it easier for counselors and students to conduct counseling that is not limited by distance and time. Cyber counseling services occur when counselors and counselors communicate remotely through devices connected to the internet network. This service has produced significant results in the effectiveness of mentoring and counseling during the COVID-19 pandemic. Until now, in the post-COVID-19 pandemic, cyber counseling services continue to be a choice for cyber counseling services. Riliv is an online counseling platform that connects people with personal problems with psychologists through text counseling, voice calls, and video calls seeking counseling. With the significant increase in the implementation of online counseling, several issues have arisen, especially regarding the application of the Code of Ethics in the implementation of online counseling. It can be concluded that counselors with cyber counseling can provide optimal services. Through technology intermediaries, counseling no longer needs to be done face-to-face, but can be done online.